2020
DOI: 10.1007/s00405-020-06096-3
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms affect short- and long-term speech recognition outcome in cochlear implant users

Abstract: Purpose To investigate the impact of the amount of depressive symptoms in cochlear implant (CI) recipients on the development of speech recognition after CI-activation up to 2 years. Design Retrospective data analysis of a German short form of the Beck Depression Inventory given at initial activation of the implant in relation to monosyllabic word recognition score at conversational level at initial activation and at 3 months, 1 and 2-year follow-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…Hence, cochlear implant users receive more cognitive and social stimulation during this period, which might positively influence their cognitive skills, communication abilities, and emotional well-being . The improvement of depressive symptoms 12 months after cochlear implantation could be attributed to the combination of improved speech perception through cochlear implantation and psychological counseling during auditory rehabilitation . Interestingly, depressive symptoms were not associated with cognitive abilities in this study’s cochlear implant users at risk for MCI, although a link between depression and cognitive decline was reported in several extensive studies .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, cochlear implant users receive more cognitive and social stimulation during this period, which might positively influence their cognitive skills, communication abilities, and emotional well-being . The improvement of depressive symptoms 12 months after cochlear implantation could be attributed to the combination of improved speech perception through cochlear implantation and psychological counseling during auditory rehabilitation . Interestingly, depressive symptoms were not associated with cognitive abilities in this study’s cochlear implant users at risk for MCI, although a link between depression and cognitive decline was reported in several extensive studies .…”
Section: Discussionmentioning
confidence: 99%
“…Carvalho et al found significant associations between speech perception performance in noise and depressive status in older hearing aid users ( 116 ). Heinze-Köhler et al identified significant associations between short- and long-term speech perception and depressive status in middle-aged and older patients after cochlear implantation ( 117 ). Please note that all these studies, including the present study, are correlational studies.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Heinze-Köhler, depressive symptoms after CI negatively correlated with monosyllabic recognition scores after 3 months and 1 year of CI. 21 In depression, verbal memory and verbal learning are impaired felt by a problem with attention and long-term memory. 22 In this study, patients had mild-moderate depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%